Effect of Chelate Iron addition And Cyanobacteria on growth and active substances of Celery Plant (Apium graveolens L.) - Warqaa Faiz Tawfeeq; Ihsan Abdl Azez Abdul Raheem (Tikrit Journal of Pure Science, 2023)
Pot experiment was conducted in the season of 2014 to study the effect of three levels of iron chelate (0, 0.5, 0.75) gm/pot and inoculated with cyanobacteria (Nostoc sp.) in two levels: T0 without inoculated, T1 with inoculated on vegetative growth characters for  celery plant. The results of interactions between iron chelate and cyanobacteria showed significant  differences with  treatments  and The treatment T1F2 gave the highest plant height (15.747 cm/plant), highest branches (4.9400 branch.plant), highest percent of dry matter of vegetative group (19.953%), biggest leaf area (6.5333 cm2/plant) and (1.2033 mg/g) of total chlorophyll in compare with lowest values of control treatment which gave the shortest plant (12.648 cm.plant), lowest branches number (3.9367 branch/plant), lowest dry matter (17.577%), smaller leaf area (4.7178 cm2/plant), and lowest total chlorophyll (0.8089 mg/g). as well as The treatment T1F2 gave the highest concentration of N، P، K، Fe & Cu That amounted to: 1.78%, 0.37200%, 1.9667%, 151.80 mg/kg & 30.967 mg/kg respectively. these were compare to the lowest concentration with control treatment as: N concentration was (1.0967%), P (0.29200%), K (1.4300%), Fe (106.3 mg/kg) and Cu (18.033 mg/kg).